KUALITAS PELAYANAN PEMBUATAN KK/ KARTU KELUARGA DI KECAMATAN BATURETNO, KABUPATEN WONOGIRI - Liliek Winarni, Joko Suranto, Faizal Dhoni Susilo, (Solidaritas, 2018)
This research aims to analyze the quality of service of making family card (KK) in Subdistrict Office Baturetno District Wonogori by using a theory of And (in the Lukman, 1999:8) about 10 dimensions of service quality improvement which then simplifies researchers in 7 dimensions of service quality improvement.The quality of public services according to Kotler (2000:25) service quality is the totality of characteristics of the goods and services showed its ability to satisfy the needs of customers, both of which appear to be obvious or hidden.The type of research used in this research is descriptive qualitative approach. As for the data collection techniques namely direct interviews with users and service providers, and documentation. The type of data in this study using primary data and secondary data.The results of this study showed that the quality of service provided by an employee of the Office of the Subdistrict of Baturetno dimensions timeliness is in compliance, in other words services already provided in a timely manner, to the dimensions of the accuracy of the service provider parties considered has not been accurate in giving pelayanankepada the community, to the dimension of the politeness and kerahaman is in compliance even very sesua, this means that service providers are already providing service with friendly and courteous. For dimensions of responsibility, the user services already give a good response. This means that the service provider is already responsible for give a service, for ease of service of process dimension of service users felt it was appropriate. This means services provided through a process that is easily understood by the user of the service, to the dimension of comfort, service users are already comfortable with the Environment Ministry, to dimension attributes, services supporting service users felt it was appropriate to their expectations.See the results of the 7 dimensions of service quality above, then researchers may conclude that the Ministry of the family card (KK) is in compliance with the wishes of the user/community service. This means that the services provided by the Subdistrict is said to be already qualified Baturetno.Â Key Words: Quality, Service, Family Card.